PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI KANTOR KEMENTRIAN AGAMA KABUPATEN SITUBONDO - Sufyan, Moh. Iqbal Abu; Hamdun, Edy Kusnadi; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The rapid development of science and technology has brought changes to human life. Can bring about changes that result in higher demands on each individual in order to further improve performance in each individual and the wider community. The purpose of this study was to analyze and examine the effect of motivation and work environment on ASN performance through work discipline as an intervening variable at the office of the Ministry of Religion, Situbondo Regency. This research is an explanatory research. The population in this study were civil servants at the office of the Ministry of Religion, Situbondo Regency. The sampling technique in this study is to use a saturated sampling technique. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that motivation has a significant negative effect on work discipline, work environment has a significant positive effect on work discipline, motivation has a significant negative effect on ASN performance, work environment has a negative but not significant effect on ASN performance, discipline work has a significant positive effect on the performance of ASN. The results of the indirect effect hypothesis test show that the motivation variable on the performance of ASN through work discipline has a significant positive effect, the work environment on the performance of ASN through work discipline has a significant positive effect.